In Defence of Cornell Realism: a Reply to Elizabeth Tropman. (30th September 2013) - Long, Joseph
Abstract Cornell realists claim, among other things, that moral knowledge can be acquired in the same basic way that scientific knowledge is acquired. Recently in this journal Elizabeth Tropman has presented two arguments against this claim. In the present article, I attempt to show that the first argument attacks a straw man and the second mischaracterizes the Cornell realists' epistemology and ends up begging the question. I close by suggesting that, given Tropman's own apparent views, her objections are also probably misplaced.